IMPLEMENTASI PEMBIASAAN MORNING QUR’AN DALAM MENINGKATKAN KEKUATAN HAFALAN SURAT PENDEK SISWA KELAS 3 MI BABUL HUDA WONOSALAM - Armilasari, Hani; Ali Mahsun (Discovery : Jurnal Ilmu Pengetahuan, 2023)
This article discusses the Morning Qur'an familiarization activities carried out by grade 3 students at Mi Babul Huda, Wonosalam, Jombang. The focus of the research that will be discussed: 1) planning the habituation program at MI Babul Huda Wonosalam Jombang, 2) implementing the habituation of the Morning Qur'an at MI Babul Huda Wonosalam Jombang in increasing students' memorization strength, 3) evaluation of the habituation of the Morning Qur'an at MI Babul Huda Wonosalam Jombang. For this research, a qualitative approach was used with a case study type of research. As well as interview, documentation and observation techniques to collect data. And the data analysis techniques used are reduction, data presentation, and drawing conclusions. In checking the validity of the data, researchers used source triangulation and technical triangulation. The results of the research related to the implementation of the Morning Qur'an habituation at Mi Babul Huda, Wonosalam, Jombang; The Morning Qur'an activity is used as an ongoing activity which is carried out before each learning activity begins. And there is a strategy of not being allowed to move to the next letter if you haven't completely memorized it. So students are not allowed to move on to the next letter if they have not completely memorized the previous letter. By using this strategy it is said to be successful because their memorization of short letters can run optimally.